2015
DOI: 10.1111/are.12759
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of rapid transfer and bioaccumulation of Microcystin‐ LR poses potential risk to freshwater prawn Macrobrachium rosenbergii (de Man)

Abstract: Microcystins accumulate in aquatic organisms and can be transferred to higher trophic levels, eventually affecting vector animals and consumers. We examined three levels of an aquatic food chain (Microcystis aeruginosa, Daphnia magna and Macrobrachium rosenbergii) to identify the transfer efficiency and risk of microcystin on prawns. Samples were analysed using ultra performance liquid chromatography‐mass spectrometry (MS)/MS and microcystin‐LR (MC‐LR) distributions in prawn tissues were studied. The results s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Studies of protein and lipids, especially fatty acid biomarkers, have also confirmed that cyanobacteria are essential for macroinvertebrate survival, especially in winter when no other food is within reach [ 70 , 95 ]. Benthic macroinvertebrates can eat cyanobacteria from benthos and plankton [ 101 , 102 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies of protein and lipids, especially fatty acid biomarkers, have also confirmed that cyanobacteria are essential for macroinvertebrate survival, especially in winter when no other food is within reach [ 70 , 95 ]. Benthic macroinvertebrates can eat cyanobacteria from benthos and plankton [ 101 , 102 ].…”
Section: Resultsmentioning
confidence: 99%
“…The relationship between cyanobacteria and benthic macroinvertebrates is not only trophic, but they can also interact biologically by simply living in the same habitat. As is known, invertebrates can be affected by cyanotoxins through their ingestion, either diluted in water and associated with particles (sediment or cyanobacterial cells) or by contact and diffusion through integument, eggs or gill membranes [ 30 , 86 , 97 , 101 , 102 , 103 , 107 ]. The harmful effect of this cohabitation has been studied more in plankton than in benthic invertebrates [ 72 , 94 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, although MCs cannot biomagnify through the food chain in most circumstances, food chain transfer of MCs has been found in some studies 47 48 . CMC concentrations in the present study were extremely high during the warmer months, and given that chironomid larvae are excellent food sources for certain fishes 22 , the MCs in T. chinensis potentially could be transferred to higher trophic levels.…”
Section: Discussionmentioning
confidence: 99%
“…Zooplankton have been clearly identified as the best bioaccumulator of cyanotoxins and may transfer them to higher trophic levels in the aquatic food web [141][142][143][144]. Mollusks have also been shown to accumulate high concentrations of cyanotoxins with hepatopancreas being the organ presenting the highest concentrations followed by the intestines [115,145].…”
Section: Bioaccumulation Of Cyanotoxins In Food Web and Impacts On Anmentioning
confidence: 99%